Formulating Public Policy for Earthquake Disaster Risk Reduction - Nefianto, Tirton (Cv. Syntax Corporation Indonesia, 2025)
When extraordinary events (hazards) occur in communities that are already at risk, people are unable to handle the consequences, which leads to disasters. The acknowledgement that a disaster poses a threat to the public is known as policy. Policymakers must establish a priority scale that takes resource scarcity into thought when designating a disaster as a public hazard. The presence of management and public policy can offer remedies and approaches to coping with calamities. his research aims to explore the strategic policies and management practices for earthquake disaster risk reduction in Indonesia. The study employs a descriptive research method with a qualitative approach, focusing on literature review and analysis of existing disaster management policies. The findings reveal that disaster management in Indonesia has evolved, with increasing emphasis on community resilience and legal responsibilities. The government has developed several disaster management models, including the Disaster Management Continuum Model and the Pre-During-Post Disaster Model, to address various stages of disaster response. Moreover, earthquake mitigation strategies such as earthquake-resistant building standards and community-based organizations are critical for reducing the impact of earthquakes. The study concludes that strategic policies and efficient public management, including resource allocation and clear institutional frameworks, are vital for addressing earthquake risks. Future policies should focus on improving the preparedness and response capabilities of both central and regional governments, ensuring a coordinated effort to mitigate the devastating effects of earthquakes.